Is There Uniformity in the Diagnosis of Learning Disability Globally? - Ashima Nehra; Ruchita Hazrati; Rhythm Makkar; Rajesh Hassija; Sanyam Bhardwaj; Apoorva Panshikar (Indian Journal of Public Health)
Learning disabilities (LDs) are a group of neurodevelopmental deficits that negatively affect the acquisition, organization, retention, comprehension, or application of age appropriate knowledge. Persons with LD lead a subsidized quality of life, especially in academic/vocational and psychosocial domains. A certificate issued by the medical boards at a state or district level is required to avail benefits such as scribes or relaxations. This may be done through a series of assessments by psychologists, special educators, or other health-care professionals. The authors aim to understand if uniformity exists in the assessment methods used for the diagnosis of LD globally and to prepare a gap analysis for the same. A systematic review was performed on English literature articles published from January 2005 to August 2023. Full-text studies reporting assessment and diagnostic methods of LD were included. A total of 1246 records were identified through a manual search of an electronic database. Seven duplicates were removed and 1174 studies were excluded based on the relevance by screening titles, abstracts, and full texts. Sixty-five studies were included and analyzed. The authors found a lack of uniformity in this diagnostic protocol, leading to uncertainty in disability certification, doctor shopping, and additional stress for the patients, as well as added burden on the government. Identification of LD requires a multistep assessment process with culturally relevant tools and norms and the participation of a multidisciplinary team of experts.